Defenders of the motherland the Tsarist elite in revolutionary Russia - Rendle, Matthew (Oxford University Press, 2010)
Matthew Rendle studies how the most powerful social groups in tsarist Russia reacted to the challenges of 1917. He argues that the alienation of elites from the tsar and their support for the Provisional Government secured the success of the revolution but the threat they posed laid the foundations of the repressive Soviet regime.